Peran Penyuluh Pertanian Dalam Peningkatan Produksi Tomat (Solanum Lycopersicum) di Desa Nitakloang, Kecamatan Nita, Kabupaten Sikka - Randi, Yanuarius (Jurnal Ilmiah Wahana Pendidikan, 2024)
Efforts to increase agricultural production cannot be separated from the participation of agricultural extension workers. The existence of agricultural extension workers can help farmers in obtaining the necessary information and technology. The high and low productivity of a farm is influenced by the difficulty of farmers in adopting new technology. This study aims to determine the level of the role of agricultural extension workers to tomato farmers and the relationship between the role of agricultural extension workers in increasing tomato production (Solanum Lycopersicum) in Nitakloang Village, Nita District. The method used in research is a survey method with a quantitative approach. The sample used was a saturated sample of 37 people, and data analysis using the Likert scale and spearman rank. The results showed that the level of the role of agricultural extension workers towards tomato farmers in Nitakloang Village, Nita District was in the very high category with a value of 90.7%. The role of agricultural extension workers as motivators, educators, catalysts, communicators, consultants, facilitators and organizers has a significant relationship in increasing tomato production. Overall, the role of extension workers has a significant relationship in increasing tomato production. This shows that the greater the role of extension workers, the more tomato production will increase.